2002
DOI: 10.1080/00365520212504
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis is Associated with a Promoter Polymorphism of Lipopolysaccharide Receptor Gene, CD14

Abstract: The promoter polymorphism of the CD14 gene at -159T plays a significant role in regulating the CD14 expression and is positively associated with ulcerative colitis, and this polymorphism may confer a genetic predisposition to ulcerative colitis. The results also support the concept that bacterial constituents may be involved in the pathogenesis of ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…Compared with the previous studies, the frequency of the CC genotype of healthy controls in Korean population (41.6%) was higher than in Chinese (15.6%) or Japanese (21.8%), whereas the TT genotype of healthy controls in Korean (14.6%) was lower than in Chinese (36.3%) or Japanese (25.4%) (12, 13). Further study in larger and diverse populations would be needed for elucidation of the association between disease susceptibility of IBD and polymorphism of CD14 gene.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Compared with the previous studies, the frequency of the CC genotype of healthy controls in Korean population (41.6%) was higher than in Chinese (15.6%) or Japanese (21.8%), whereas the TT genotype of healthy controls in Korean (14.6%) was lower than in Chinese (36.3%) or Japanese (25.4%) (12, 13). Further study in larger and diverse populations would be needed for elucidation of the association between disease susceptibility of IBD and polymorphism of CD14 gene.…”
Section: Discussioncontrasting
confidence: 71%
“…Previously, in several reports from Western countries, gene polymorphisms of the CD14 was found to be associated with the development of IBD, more so in the development of CD than in UC (9, 10). However, in Japanese population, the same genotype is associated with UC but not with CD (12, 15), and another study investigating Chinese patients failed to demonstrate any association (13). In our results, T allele and TT genotype frequencies of CD14 gene were significantly higher in IBD patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 95%
“…The relevance of a variant on the CD14 gene at position c.1-260C>T has been investigated for CD and UC by three other groups [34,35,36,37]. One of these studies [36] looked at a Japanese cohort of 101 UC patients, 82 CD patients and 123 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies [36] looked at a Japanese cohort of 101 UC patients, 82 CD patients and 123 healthy controls. The authors reported T allele frequencies of 57.4% for UC, 48.2% for CD and 44.7% for healthy controls as well as TT homozygote genotype frequencies of 37.6% for UC, 25.5% for CD and 23.6% for healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ly6C hi monocytes differentiate into dominant pro-inflammatory effector cells in the inflamed gut due to the up-regulation of TLR2 and NOD2 (Zigmond, et al, 2012). Furthermore, CD14-expressing macrophages that are more sensitive to LPS (Lee, et al, 1992) are increased in the intestinal mucosa of IBD patients compared to healthy controls (Obana, et al, 2002) and might contribute to the initiation and maintenance of the inflammatory environment. Thus, not only the regulation of the respective target molecules itself, but also the modulation of receptors and signaling pathways influenced by their expression might represent promising targets for clinical intervention.…”
Section: Discussionmentioning
confidence: 99%